The structure of human ATG9A and its interplay with the lipid bilayer. Issue 12 (1st December 2020) - Guardia, Carlos M.; Christenson, Eric T.; Zhou, Wenchang; Tan, Xiao-Feng; Lian, Tengfei; Faraldo-Gómez, José D.; Bonifacino, Juan S.; Jiang, Jiansen; Banerjee, Anirban
ABSTRACT: ATG9, the only transmembrane protein in the core macroautophagy/autophagy machinery, is a key player in the early stages of autophagosome formation. Yet, the lack of a high-resolution structure of ATG9 was a major impediment in understanding its three-dimensional organization and function. We recently solved a high-resolution cryoEM structure of the ubiquitously expressed human ATG9A isoform. The structure revealed that ATG9A is a domain-swapped homotrimer with a unique fold, and has an internal network of branched cavities. In cellulo analyses demonstrated the functional importance of the cavity-lining residues. These cavities could serve as conduits for transport of hydrophilic moieties, such as lipid headgroups, across the bilayer. Finally, structure-guided molecular dynamics predicted that ATG9A has membrane-bending properties, which is consistent with its localization to highly curved membranes.